Students’ Perception on Effectiveness of Pathology Teaching in Phase 1 Medical Program at UCSI University - San, San Oo (2016)
A sound knowledge of pathology is essential to clinical practice. This study explored the students’ perception on effectiveness of pathology teaching in Phase 1 medical program at UCSI University. Materials and methods: A cross sectional descriptive study was performed in 83 medical students from clinical phase by using pretested questionnaire which comprised 46 statements assessing the students’ perception on subject, teaching–learning methods, availability of facilities and resources, and effectiveness of pathology teaching. Results: Out of 83, 55.4% perceived that pathology is interesting and 81.9% responded as a challenging subject. More than half of the students were satisfied with general and systemic pathology teaching and agreed that they were made easy to understand the learning topics by lectures combined with museum and directed-self learning, and also by integrated with other basic science subjects. Students perceived that lectures are more effective than self-learning and knowledge obtained from lectures was more than that of problem-based learning. Over 60% agreed that phase 1 pathology teaching is helpful for better understanding of clinical teaching and they were given adequate foundation for clinical years. Conclusion: Although students were satisfied with the methods of teaching of pathology in Phase 1, teaching plan should be reviewed to create students’ centered, more active learning classroom persuading students to perceive more interest on the subject. Because of half of the students who did not agree and who gave neutral responses to the statement on adequacy of pathology knowledge, the contents in curriculum should be reviewed for further improvement.